2022
DOI: 10.3389/fpubh.2022.865699
|View full text |Cite
|
Sign up to set email alerts
|

Research on Monetary Policy Implementation and Industrial Structure Transformation Under COVID-19—Evidence From Eight Economic Zones in Mainland China

Abstract: The outbreak of COVID-19 has brought a serious impact on the economies of various countries, monetary policy needs to play a role in stimulating economic recovery when the economy encounters a serious negative impact. Since the recurrent outbreak of COVID-19 has caused great obstacles to the normal economic exchanges between countries, it has become particularly important to build the domestic market and optimize the industrial allocation at this time. This paper focuses on studying the dynamic impact of China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…This hinders precise measurement of monetary quantity and leads to reduced effectiveness of quantitative monetary policy tools. In contrast, interest rates can overcome these shortcomings and provide better controllability over targets compared to quantitative tools (Zhou et al, 2022). Therefore, price-based monetary policy tools are more effective in the long term.…”
Section: Nonlinearity Of Various Monetary Policy Transmissionmentioning
confidence: 99%
“…This hinders precise measurement of monetary quantity and leads to reduced effectiveness of quantitative monetary policy tools. In contrast, interest rates can overcome these shortcomings and provide better controllability over targets compared to quantitative tools (Zhou et al, 2022). Therefore, price-based monetary policy tools are more effective in the long term.…”
Section: Nonlinearity Of Various Monetary Policy Transmissionmentioning
confidence: 99%
“…Compared to other developed countries, China's capital market lacks sufficient self‐regulating mechanisms, which poses risks to its healthy operation. Therefore, government macro‐control is essential to ensure stability in China's market economy (Zhou et al, 2022). The government conducts macroeconomic regulation by publishing related economic policies, and fluctuations of policies cause economic entities to be unable to predict whether, when, and how the government will change current economic policies (Gulen & Ion, 2016), which indicates that the external EPU faced by enterprises increases.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Faced with the unpredictable domestic and international situation and the severe impact of COVID-19, the economy subsystem has been the most affected. [53] showed that COVID-19 has brought negative impacts on the economy, destroyed the original stability of the economic system, and increased the uncertainty of the effect of monetary policy regulation. Industries in most economic regions under COVID-19 lag behind the impact of monetary policy for a longer time.…”
Section: Evaluation Of the Development Index Of Subsystemmentioning
confidence: 99%